2023
DOI: 10.3803/enm.2022.1588
|View full text |Cite
|
Sign up to set email alerts
|

Association between N-Terminal Prohormone Brain Natriuretic Peptide and Decreased Skeletal Muscle Mass in a Healthy Adult Population: A Cross-Sectional Study

Abstract: Background: Sarcopenia, an age-related decline in muscle mass and function, is one of the most important health problems in elderly with a high rate of adverse outcomes. However, several studies have investigated the prevalence of sarcopenia in the world, the results have been inconsistent. The current systematic review and meta-analysis study was conducted to estimate the overall prevalence of sarcopenia in both genders in different regions of the world. Methods: Electronic databases, including MEDLINE (via P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…Interestingly, NT-proBNP showed negative, significant clinical correlations with quality muscle-related parameters determined by different techniques, suggesting that nutritional impact on muscle mass is also reflected in heart functionality. A previous study by our group also revealed these clinical correlations [20], and a recent report in healthy adults described a higher prevalence of increased serum NT-pro BNP in people with low skeletal muscle mass [28].…”
Section: Discussionsupporting
confidence: 71%
“…Interestingly, NT-proBNP showed negative, significant clinical correlations with quality muscle-related parameters determined by different techniques, suggesting that nutritional impact on muscle mass is also reflected in heart functionality. A previous study by our group also revealed these clinical correlations [20], and a recent report in healthy adults described a higher prevalence of increased serum NT-pro BNP in people with low skeletal muscle mass [28].…”
Section: Discussionsupporting
confidence: 71%